Effect of Collaborative Instructional Approach on Personality Traits in Geometry Achievement Among Secondary School Students in Zing Education Zone, Taraba State - Bulus, Shiaki O.; Yukwa, Bernard A. (International Journal of Education, Management, and Technology, 2025)
This study investigates the impact of a collaborative instructional approach on the academic achievement of secondary school students in geometry, with particular attention to variations across personality traits in Zing Education Zone, Taraba State, Nigeria. The study was guided by four specific objectives, including the assessment of achievement levels among students with agreeableness, conscientiousness, and openness to experience traits when taught using either the collaborative instructional approach or the traditional lecture method. A quasi-experimental research design, incorporating both pre-test and post-test groups, was employed. The sample consisted of 295 students categorized based on their dominant personality traits. Data collection utilized a validated instrument with a reliability coefficient of 0.95 (Cronbach’s alpha). Descriptive statistics, specifically mean and standard deviation, were used to address the research questions, while hypotheses were tested using analysis of covariance (ANCOVA) at the 0.005 significance level. The findings revealed, among other results, that students characterized by openness to experience demonstrated lower academic achievement in geometry when taught using the collaborative instructional approach compared to their counterparts taught with the lecture method. Based on these findings, the study recommends targeted professional development interventions, including seminars and workshops for teachers in the Zing Education Zone. These programs should focus on enhancing content mastery and equipping educators with strategies to tailor instruction to the diverse personality profiles of their students, thereby improving learning outcomes.